Determination of the strong coupling constant from the inclusive jet cross section in pp̄ collisions at s=1.96TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; et al. (American Physical Society (APS), 2009)
We determine the strong coupling constant αs and its energy dependence from the pT dependence of the inclusive jet cross section in pp̄ collisions at s=1.96TeV. The strong coupling constant is determined over the transverse momentum range 50<pT<145GeV. Using perturbative QCD calculations to order O(αs3) combined with O(αs4) contributions from threshold corrections, we obtain αs(MZ)=0.1161-0.0048+0.0041. This is the most precise result obtained at a hadron-hadron collider. © 2009 The American Physical Society.